Kommunikativ adfærd i virksomhedsrepræsentationer - Hermann, Helle (HERMES - Journal of Language and Communication in Business, 2001)
This article presents the results of an empirical pilot-study of Danish and French company presentations. The aim of the study is to establish how human relations manifest themselves in the linguistic surface. The results are divided into horizontal (Distance) and vertical (Authority) relations. The study is based on the concepts of Face and Facework and through a systematization of the chosen Facework strategies differences between Danish and French communicative behavior are shown. The Danish companies appear to have a communicative profile indicating a wish to establish close relations with the reader and a greater need of selfpraise than the French companies.